The Labour Conference and after, three viewpoints : Labour Party, Trade Union and ILP : the answer to Vansittard - Edwards, Bob; Monte, Hilda (London : National Labour Press, 1943)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Labour Party (Verenigd Koninkrijk).; Wereldoorlog 2; Groot-Brittannië.